Family carers’ experiences of managing older relative’s medications: Insights from the MEMORABLE study - Lawson, S; Mullan, J; Wong, G; Zaman, H; Booth, A; Watson, A; Maidment, I (Elsevier, 2021)
Objective To explore the burdens experienced by family carers who support older relatives to manage their medications at home.